2014
DOI: 10.1007/s00429-014-0909-3
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-A deletion increases the plasticity of the optokinetic response and changes retinal projection organization in the adult mouse visual system

Abstract: The inhibitory action of Nogo-A on axonal growth has been well described. However, much less is known about the effects that Nogo-A could exert on the plasticity of neuronal circuits under physiological conditions. We investigated the effects of Nogo-A knock-out (KO) on visual function of adult mice using the optokinetic response (OKR) and the monocular deprivation (MD)-induced OKR plasticity and analyzed the anatomical organization of the eye-specific retinal projections. The spatial frequency sensitivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Another inhibitory myelin protein, NOGO was reported in many studies to play a cardinal role in the inhibitory effect of myelin243637. Suppressing its expression in neural cultures as well as in animal models prevented the axonal outgrowth inhibition38394041. Preliminary results of NOGO expression by immunofluorescence staining showed an elevation in the cortices of the injured brains and that GM1 administration prevented this elevation (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Another inhibitory myelin protein, NOGO was reported in many studies to play a cardinal role in the inhibitory effect of myelin243637. Suppressing its expression in neural cultures as well as in animal models prevented the axonal outgrowth inhibition38394041. Preliminary results of NOGO expression by immunofluorescence staining showed an elevation in the cortices of the injured brains and that GM1 administration prevented this elevation (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…We have previously reported that glia-specific inactivation of Nogo-A increased retinal ganglion cell plasticity after optic nerve injury (Vajda et al, 2015) and after monocular deprivation in intact animals (Guzik-Kornacka et al, 2016). In the brain, the Nogo-A-S1PR2 ligandreceptor pair may also operate in the mechanisms controlling blood vessel plasticity after stroke.…”
Section: Discussionmentioning
confidence: 96%
“…To evaluate the visual acuity of freely moving mice, the optokinetic reflex was tested using OptoDrum system (Striatech GmbH Vor dem Kreuzberg, Tübingen, Germany). In brief, mice (6-9/group) were placed on a platform in the middle of an arena surrounded by four computer screens while moving gratings of different spatial frequencies were passed on the monitors 36,37 . The reflexive tracking movement of the mouse neck in the temporal-to-nasal direction allowed to evaluate the visual response of the two eyes separately by changing the direction of the visual stimulus.…”
Section: Optokinetic Reflex Testmentioning
confidence: 99%
“…This mechanism deserves to be tested in the injured visual system. It may allow to explain why the plasticity of RGC terminals is increased in the dorso lateral geniculate nucleus of Nogo-A KO mice after monocular deprivation, for example 36 . A similar mechanism may operate after retinal excitotoxicity.…”
Section: Retinal Excitotoxicity Increases Vitreal Nogo-a Proteinsmentioning
confidence: 99%